Silicon extraction from x-ray amorphous soil constituents: a method comparison of alkaline extracting agents - Stein, Mathias; Puppe, Daniel; Kaczorek, Danuta; Buhtz, Christian; Schaller, Jörg (Frontiers in Environmental Science, 2024)
The growing interest in amorphous silica (ASi) within the fields of soil science and ecology underscores the necessity for a reliable protocol to estimate ASi contents in soil. Alkaline wet chemical extraction methods are commonly employed for silicon (Si) extraction from operationally defined (x-ray) amorphous Si phases or short-range ordered mineral phases in soils and marine sediments. In our study we conducted a comparative analysis of four alkaline extraction methods (1% sodium carbonate, 0.5 M sodium carbonate, 0.2 M sodium hydroxide, and 0.1 M Tiron), assessing their extraction selectivity as well as effectiveness using soils artificially enriched with varying, defined amounts of ASi. While extraction effectiveness was evaluated by determining the recovery rate of initially added ASi, extraction selectivity was determined by measuring aluminum (Al) and iron (Fe) concentrations as indicators of the dissolution of non-target mineral phases. Microwave plasma atom emission spectrometry was used to analyze Al, Fe, and Si concentrations in the extracts. Our results indicate that extraction with 0.2 M sodium hydroxide yields the best outcomes in terms of both extraction effectiveness and selectivity. This more recent extraction technique is conducted at the most alkaline pH (13.3) of all four methods tested, but at ambient temperature (21°C) decreasing the dissolution of non-target mineral phases. Though, no wet-chemical extraction used on heterogeneous samples like soil is precisely selective, and thus able to quantify the target analyte only. Hence, data obtained by such procedures still need to be interpreted with caution considering all their limitations.